THE ART OF USING CULTURAL CORPUS IN THE TALE OF KIEU - Võ Minh Hải (Tạp chí Khoa học Đại học Đà Lạt)
This article discusses some characteristics of the artistic style that Nguyen Du used in the corpus system of “The Tale of Kieu”. By analyzing the characteristics of the language, the article researches the unique combination of the many corpus systems used to create the cultural depth and immortal value of this work of Vietnamese Nom literature. The article also honors the contributions of Nguyen Du and “The Tale of Kieu” to the language of Vietnamese classical literature.